(untitled) (European Journal of Pure and Applied Mathematics, 2023)
In this paper, an n-th order neutral nonlinear differential equation is studied. By using the Banach contraction principle, some sufficient conditions are established for the existence of nonoscillatory solutions of nonlinear n-th order neutral differential equation. An example is included to illustrate the results obtained.